The Transcription Factor MdERF78 Is Involved in ALA-Induced Anthocyanin Accumulation in Apples - Fang, Xiang; Zhang, Liuzi; Wang, Liangju (Frontiers in Plant Science, 2022)
Abstract: As a friendly plant growth regulator to environment, 5-Aminolevulinic acid (ALA), has been widely used in plant production, such as fruit coloring, stress resistant, and so on. Previous studies have identified some genes has the function in the anthocyanin accumulation induced by ALA. However, the regulatory mechanism has not been revealed. In the current study, we proposed that an ALA-responsive transcription factor, MdERF78, regulated the anthocyanin accumulation. MdERF78 overexpressed in apple peels or calli resulted in a significant increase of anthocyanins, while MdERF78 interference had an opposite trend. Furthermore, the anthocyanin accumulation induced by MdERF78 overexpression was enhanced by exogenous ALA treatment, suggesting that MdERF78 may be located in of regulatory routes of ALA in inducing anthocyanin accumulation. Y1H and Dual luciferase reporter assays revealed that MdERF78 bound to the promoters of MdF3H and MdANS directly, and activated their expressions. Additionally, MdERF78 interacted with MdMYB1, and enhanced the transcriptional activity of MdMYB1 to its target gene promoters. Based on these, it can be concluded that MdERF78 has a positive function in ALA-induced anthocyanin accumulation via the MdERF78-MdF3Hpro/MdANSpro and MdERF78-MdMYB1-MdDFRpro/ MdUFGTpro/MdGSTF12pro regulatory network. These findings provide new insights into the regulatory mechanism of ALA-promoted anthocyanin accumulation.